Antibacterial Activity Test of Ethanol Extract of Fiddlehead (Diplazium esculentum) Agains the Growth of Staphylococcus aureus and Escherichia coli Bacteria in Vitro: Uji Aktivitas Antibakteri Ekstrak Etanol Pakis Sayur (Diplazium esculentum) terhadap Pertumbuhan Bakteri Staphylococcus aureus dan Escherichia coli secara in Vitro - Saragih, Hana Dipa Christine; Agustrina, Rochmah; Farisi, Salman; Sumardi (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2025)
Infectious diseases are a significant public health issue in both developed and developing countries. Infectious diseases are caused by the bacteria Staphylococcus aureus and Escherichia coli, which cause high rates of morbidity and mortality. Treatment of infectious diseases caused by pathogenic bacteria generally uses antibiotics, but the continuous use of antibiotics can have side effects such as the occurrence of antibiotic resistance. Diplazium esculentum is one of the medicinal plants that is often used to treat infectious diseases. The content of secondary metabolite compounds contained in D. esculentum includes saponins, steroids, alkaloids, tannins, glycosides, triterpenoids, phenols, flavones, and flavonoids. This study aims to determine the effect of bacteriostatic activity of ethanol extract of D. esculentum and its effective concentration in inhibiting the growth of pathogens S. aureus and E. coli. The study was conducted using a Randomised Complete Block Design (RAKL) with four concentrations of ethanol extract of vegetable fern, namely 20%, 33%, 43%, and 50%. As a positive control, the antibiotic chloramphenicol was used and the negative control used sterile distilled water. Data in the form of inhibition zone diameter formed from each treatment were analysed using Kruskal Wallis non-parametric test and continued with Mann Whitney Post Hoc test. The results of the study showed that the concentration of ethanol extract of D. esculentum showed bacteriostatic activity against S. aureus bacteria at concentrations of 43% and 50% with inhibition zones of 6.52 mm and 5.55 mm, as well as E. coli bacteria at concentrations of 43% and 50% with inhibition zones of 5.11 mm and 4.37 mm, but was not effective in inhibiting the growth of S. aureus and E. coli bacteria.